Maternal manganese activates anti-apoptotic-related gene expressions via miR-1551 and miR-34c in embryonic hearts from maternal heat stress (Gallus gallus). (August 2019) - Liao, Xiudong; Zhu, Yongwen; Lu, Lin; Li, Wenxiang; Zhang, Liyang; Ji, Cheng; Lin, Xi; Luo, Xugang
Abstract: MicroRNAs (miRNAs) expressions are altered by maternal stresses and nutritional status. Our previous study has demonstrated that maternal manganese (Mn) addition could protect chick embryos against maternal heat stress via enhancing anti-apoptotic ability in embryonic hearts. The objective of this study was to investigate whether this protective effect could be achieved via miRNA mechanisms, and also be sustained in offspring broilers. A completely randomized design with a 2 (maternal normal and high temperatures: 21 and 32 °C) × 2 (maternal control basal diet and the basal diet + 120 mg Mn/kg) factorial arrangement of treatments was adopted. Totally 96 broiler breeder hens were allotted to 4 treatments with 6 replicates. Subsequently, 24 hatched chicks from each maternal treatment were divided into 6 replicates. Maternal supplemental 120 mg Mn/kg reduced the increased expressions of miR-1551 and miR-34c in hearts of offspring embryos but not broilers under maternal heat stress. B-cell CLL/lymphoma 2 ( BCL2 ) and NF-κB-inducing kinase ( NIK ) genes related to anti-apoptotic ability were identified as direct targets for miR-1551 and miR-34c, respectively. Under maternal heat stress, maternal supplemental 120 mg Mn/kg activated target BCL2 expression and NIK-dependent NF-κB pathway via mediating miR-1551 and miR-34c expressions in hearts of offspring embryos rather than broilers. Highlights: Maternal heat stress increases the miRNAs expressions in embryonic hearts. Anti-apoptotic genes are targeted by miRNAs. Maternal supplemental 120 mg Mn/kg activates anti-apoptotic gene expressions in embryos by miRNAs.